Peningkatan Kapasitas SDM Kementerian Pendidikan Timor Leste Melalui Pelatihan Learning Management System Berbasis Moodle di Universitas Dinamika - Vivine Nurcahyawati; Erwin Sutomo (Jurnal Ragam Pengabdian, 2025)
Moodle-based Learning Management System (LMS) training is one of the solutions to enhance digital literacy among educational staff, especially in government institutions engaged in the field of education. This activity is carried out by Universitas Dinamika in collaboration with DPD PPGI East Java and the Ministry of Education of Timor Leste, as a form of community service aimed at enhancing human resource capacity in the era of digital transformation. The main objective of this activity is to equip the staff of the Timor Leste Ministry of Education with technical knowledge and skills in using the Moodle LMS, ranging from user account management, lesson material preparation, to the use of evaluation features and interactive forums. The implementation method of the activity includes a 6-hour hands-on face-to-face training, supported by digital training modules and the internal LMS system of Universitas Dinamika, MyBrilian. Evaluation was conducted using a qualitative approach through observation and participant satisfaction questionnaires. The results show a change in attitude towards the use of technology in supporting their work. This activity has an impact on increasing participants' digital readiness, strengthening institutional capacity in e-learning implementation, and opening up opportunities for sustainable international collaboration. Universitas Dinamika, through this activity, plays a role in strengthening digital literacy in the regional area and makes a tangible contribution in the field of educational technology.